Pygoscelis papua - Hospitaleche, Carolina Acosta; Soto-Acuña, Sergio (Zenodo, 2023)
P. papua (MLP 38, MLP 449, MLP 451, MLP 463, MLP 468), Published as part of Hospitaleche, Carolina Acosta & Soto-Acuña, Sergio, 2023, A small penguin cranium (Aves, Spheniscidae) from the Late Miocene of Bahía Inglesa Formation, Atacama Desert, Northern Chile, pp. 233-244 in Comptes Rendus Palevol 22 (13) on page 237, DOI:10.5852/cr-palevol2023v22a13, http://zenodo.org/record/14233130